2021
DOI: 10.1007/s00431-021-03984-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of changes in preterm delivery and stillbirths during COVID-19 lockdown in a European region

Abstract: Preliminary data in Europe have suggested a reduction in prematurity rates during the COVID-19 pandemic, implying that contingency measures could have an impact on prematurity rates. We designed a population-based prevalence proportion study to explore the potential link between national lockdown measures and a change in preterm births and stillbirths. Adjusted multivariate analyses did not show any decrease in preterm proportions during the lockdown period with respect to the whole prelockdown period or to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 9 publications
1
59
2
1
Order By: Relevance
“…In contrast, Wood et al observed no reduction in preterm birth rates [ 19 ]. Other studies reported no changes during the lockdown period [ 20 , 15 , 21 , 22 ]. Different approaches to birth outcomes research might explain the differences between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Wood et al observed no reduction in preterm birth rates [ 19 ]. Other studies reported no changes during the lockdown period [ 20 , 15 , 21 , 22 ]. Different approaches to birth outcomes research might explain the differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to studies that reported a lower rate of adverse pregnancy outcomes, our findings in regard of reduced preterm births and low birth weight during the lockdown may be explained by a variety of factors. The latter include greater focus on hygiene and home confinement, less work-related strain, more opportunities for rest and nutritional support, the support systems provided during the lockdown, reduced exposure to infection [ 18 , 21 ] as well as the postponement or suspension of medical interventions leading to iatrogenic preterm delivery. According to Phillip et al the Covid-19 lockdown was likely to cause socio-environmental changes and behavioral modifications, and thus exert a beneficial impact on pregnancies during this period [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Following this finding, similar reductions in PTBs were reported from the Netherlands, 1 Japan, 4 Italy, 5 Tennessee, 6 New York, 7 Israel, 8 and the USA 9 and a report from Ireland described a reduced proportion of very low birth weight babies. 10 However, smaller studies from California, 11 Philadelphia, 12 Israel, 13 Spain, 14 and London, 15 as well as a recent nationwide Swedish study 16 could not confirm these findings.…”
Section: Introductionmentioning
confidence: 93%
“…What has been clear so far is that hospital admissions have decreased; for example, a study taking place during an interval of 10 weeks found that there was a 43.2 percent decrease in hospital admissions and a 66.4 percent decrease in reported obstetric emergencies compared to the previous year’s similar calendar months [ 12 ]. However, researchers found that either the proportions of preterm live births decreased during the pandemic [ 13 ] or that they did not differ during the lockdown [ 14 ], or the opposite, with higher preterm birth rates happening during the COVID-19 pandemic, compared with a period before the pandemic [ 15 ]. Thus, what they all have in common is analyzing a short period of two or three months during the full lockdown in the Spring of 2020 and a possible explanation that maternal activity might be related to a decreased risk of preterm delivery, as the study suggests.…”
Section: Introductionmentioning
confidence: 99%